Ocorrência de crryptosporidium spp, em animais exóticos de companhia no Brasil: Milena Sato de Souza. - - Souza, Milena Sato de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Infection by some species or genotypes of Cryptosporidium represents a potential risk to public health, mainly because of the morbidity and mortality in children from zero to five years of age and in immunocompromised patients. Although there are some reports of Cryptosporidium infection in exotic animals, the participation of these animals in the epidemiology of human cryptosporidiosis is uncertain and studies on this topic is still rather scarce. The aim of this study was to determine the occurrence as well as to perform the molecular classification of Cryptosporidium spp. in faecal samples of exotic animals raised as pets in Brazil. A total of 386 faecal samples from six species of exotic animals was collected and stored in a solution 5% potassium dichromate at 4°C. The oocysts were purified by centrifugal sedimentation water-ether, followed by genomic DNA extraction and the performance of the nested-PCR to amplify partial gene fragment of 18S rRNA. Positivity for Cryptosporidium spp. was obtained in 11.40% (44/386) of samples. The sequencing of the amplified fragments allowed the identification of Cryptosporidium tyzzeri (Cryptosporidium mouse genotype I) on mice (Mus musculus), Cryptosporidium muris in mice, hamster (Mesocricetus auratus and Cricetulus griseus) and chinchilla (Chinchilla lanigera), Cryptosporidium parvum in chinchila and Cryptosporidium sp. in guinea pig (Cavia porcellus). The results of this study show that there are a variety of species of Cryptosporidium spp. present in exotic animals company in Brazil. The data suggest that these animals may have zoonotic potential and participate in the epidemiology of human cryptosporidiosis
Keywords: Reação em cadeia de polimerase; Saúde pública; Zoonoses; Animais exóticos; Cryptosporidium; Epidemiology